The Gut Microbiota of the Greater Horseshoe Bat Confers Rapidly Corresponding Immune Cells in Mice - Shan Luo; Xinlei Huang; Siyu Chen; Junyi Li; Hui Wu; Yuhua He; Lei Zhou; Boyu Liu; Jiang Feng (Animals)
Background: Emerging infectious diseases threaten human and animal health, with most pathogens originating from wildlife. Bats are natural hosts for many infectious agents. Previous studies have demonstrated that changes in some specific genes in bats may contribute to resistance to viral infections, but they have mostly overlooked the immune function of the bat gut microbiota. Aims: In this study, we used fecal transplants to transfer the gut microbiota from the Greater Horseshoe Bat (Rhinolophus ferrumequinum) into mice treated with antibiotics. The gut microbiota changes in mice were detected using 16S rRNA high-throughput sequencing technology. Flow cytometry was used to detect changes in associated immune cells in the spleen and mesenteric lymph nodes of the mice. Results: The results showed that the gut microbiota of mice showed characteristics of some bat gut microbiota. The Greater Horseshoe Bat’s gut microbiota changed some immune cells’ composition in the spleen and mesenteric lymph nodes of mice and also conferred a faster and higher proportion of natural killer cell activation. Conclusion: This result provides new evidence for the regulatory immune function of bat gut microbiota and contributes to a deeper insight into the unique immune system of bats.